Factors Affecting Going Concern Audit Opinions In Companies Listed On The Indonesia Stock Exchange In 2020–2022 - Rahadian Amrullah; Fadli Nuryasin (Asosiasi Dosen Muda Indonesia, 2025)
Going concern audit opinion is an opinion issued by auditors to ensure whether the company can maintain its survival. There are many factors that form the basis and guidelines for auditors in issuing going concern opinions and assessing the fairness of financial statements. This study aims to determine whether there is a positive potential for audit tenure, financial leverage and company growth on going concern audit opinions in companies listed on the IDX in 2020–2022. Using purposive sampling technique, a sample of 60 manufacturing companies was obtained. The company's annual report is the source of data in this study. The research test tool uses SPSS version 25. The T test is used to analyze the relationship between variables. The results of the research test state that audit tenure, financial leverage have an effect and company growth has no effect on going concern audits.